Perancangan Web Komik Angling Dharma Sebagai Pengenalan Cerita Rakyat Jawa Timur Kepada Dewasa 18-25 Tahun - Febyanti, Feby; Ayuswantana, Alfian Candra; Wulandari, Sri (Universitas Komputer Indonesia, 2023)
In this modern era, it is necessary to design a culture in Indonesia that attracts the interest of the younger generation so they don't forget their country's identity. Literature is one area of culture that can be raised. This design aims to introduce one of Indonesian literature, namely the folklore of Angling Dharma to the target age group of 18-25 years. The media that is effectively used is comics. There are several types of comics, one of which is web comics. Web comics were chosen because this type of comic is cheaper and has a wider reach than printed comics. The design will use a qualitative descriptive method to analyze interview data, questionnaires and feedback which will then be followed by the implementation of the design concept, and then the implementation of the design. The design will focus on the fantasy genre as the main attraction. From the results of the research, designers can find out how to get the younger generation interested in learning Angling Dharma folklore. Like the character designs in an anime/cartoon style, the main characters have issues that are close to the reader, and the setting designs are fantasy-like. With this design, it is hoped that the Angling Dharma web comic can attract the curiosity of the younger generation.